Conversor Boost pré-regulador com funções CFP e CC-CC integradas para sistemas UPS utilizando célula a combustível como fonte auxiliar de energia - Maciel, Renato Santiago (2014)
This work presents the development of a Boost converter with a passive resonant soft-commutation cell (ZCS-ZVS) for application as a pre-regulator converter used for an online uninterrupted power supply system, using a fuel cell as auxiliary power source. The control strategy is implemented using a Digital Signal Processor (DSP) and is based on the average current control method for sinusoidal input line current imposition, in order to respect the limits of current harmonic distortion imposed by the IEC 61000-3-2, assuring therefore high input power factor. In this work presents detailed the operation principle of the proposed converter, qualitative and quantitative analysis, design specifications, simulation and experimental results obtained from the implementation of a 500W prototype.